A survey on threshold methods of image segmentation - FU Feng; YING Yi-bin (浙江大学学报. 农业与生命科学版, 2003)
The threshold method is one of the most fundamental methods of image segmentation, and it has been applied in many fields. The threshold methods of image segmentation are surveyed in this article, especially those based on the gray level histogram.